Wheelchair Control Using Bluetooth-Based Electromyography Signals - Yoga Eko Prasetyo; Hindarto Hindarto; Syamsudduha Syahrorini; Arief Wisaksono (Journal of Computer Networks, Architecture and High Performance Computing, 2023)
In modern times like this, many wheelchairs have been developed with various controls, ranging from manual ones, namely by being pushed by other people or using their hands to turn the wheel, to automatic ones, such as electric wheelchairs that use joysticks and Electromyography control. The control of the electromyography signal utilizes muscles that can still be used to move the wheelchair, in this case, using the hand muscles. The use of a Bluetooth wireless system in sending electromyography signals aims to facilitate the use of a wheelchair without interference from the many connected cables so that users are more flexible in placing the electromyography sensor on the user's hand muscles. By placing the electromyography sensor on the user's arm, the electromyography sensor detects a contraction or relaxation, which is indicated by the LED flame. The output value of the sensor will be compared with a predetermined limit value. When the value is greater than the limit value, it will produce a logic low; when the value is less than the limit value, it will build a logic high. The Arduino microcontroller will calculate every low logic. The results of these calculations will be processed into serial data. The serial data will be sent to the HC-05 enslaved person via the HC-05 master wirelessly. The motor driver will execute the data so that it produces motion forward, backward, turn right, turn left and stop. It is hoped that this tool can help individuals with limited movement so that they do not have difficulty in mobility.